Human peripheral B cell development - Holmqvist, Joel (My University, 2011)
Since the middle of the nineties, our understanding of human peripheral B cell development has gradually increased. Today, the B cell compartment has been divided into three main populations; transitional, naive and memory B cells. In Mats Bermark's laboratorium, a cell surface marker identifying a novel peripheral B cell population has been found. The work performed during this thesis aimed to characterize the novel B cell population by comparing it with the major already described peripheral B cell populations. Novel B cells were found to be smaller than memory B cells. The antibody genes were found to contain less mutations than those of memory B cells. Furthermore, novel B cells were found to be less prone to enter apoptosis than transitional B cells. A screening experiment using flow cytometry added support to the hypothesis that the novel B cells are different from the already described populations. The results suggests that the novel B cell population is a distinct subpopulation post- or parallel to the naive population. Novel B cells might be able to differentiate into IgM+ memory B cells. In order to verify this, new experiments are needed
Keywords: Energi; Livsvetenskaper; Industriell bioteknik; Energy; Life Science; Industrial Biotechnology